OWE-11 The prevalence and burden of Rome IV functional colorectal disorders in ulcerative colitis. (June 2019) - Nigam, Gaurav B; Limdi, Jimmy K; Hamdy, Shaheen; Vasant, Dipesh H
Abstract : Introduction: Despite advances in Ulcerative Colitis (UC) therapies, many patients suffer refractory symptoms in the absence of active inflammation. For this group, treatment remains challenging, with a paucity of therapeutic options. In this prospective, ongoing study, we aim to determine the prevalence and burden of functional colorectal disorders in patients with quiescent UC using validated questionnaires. Methods: In a cross-sectional study, consecutive patients with UC attending Inflammatory Bowel Disease (IBD) clinics were invited to participate. Patients completed a series of validated questionnaires; including Hospital Anxiety and Depression Scale (HADS), the Rome IV diagnostic questionnaire for functional gastrointestinal disorders (FGIDs), an IBD-QoL score and the IBD-control questionnaire. Participants were requested to return a Faecal Calprotectin (FCP) within 2 weeks of completing questionnaires. Quiescent UC was defined as IBD-control 8 score ≥13 and IBD-control-VAS ≥85, and/or FCP levels ≤250 (where available, FCP data were used in preference to IBD-control to classify UC activity). Based on Rome IV diagnosis and UC disease activity (active or quiescent), patients were divided into groups and data compared using non-parametric tests. Results: Overall, n=97 UC patients (n=50 males, mean age 48 (range 1–2)) participated. 41/97, (42%) UC patients met the Rome IV diagnostic criteria for ≥1 FGIDs (irritable bowel syndrome n=26, functional constipation n=6 and faecal incontinence (FI) n=22). Disease activity data (IBD-control and/or FCP) were available for all patients, and based on these 61/97, 63% had quiescent UC. Within the quiescent UC group, 25/61 (41%) met the Rome IV diagnostic criteria for ≥1 FGIDs (irritable bowel syndrome n=14, functional constipation n=3 and FI n=13). Within the active UC group, those with co-existing FGIDs, compared to those without FGIDs, had significantly worse median QoL scores (P=0.02), higher HADS-depression (P=0.005) and HADS-anxiety (P=0.05). By contrast, in those with quiescent UC, those with an FGID did not have different median HADS scores (depression P=0.15, anxiety P=0.62) or IBD-QoL scores (P=0.20), compared those without FGIDs. Conclusion: This study is one of the first to use Rome IV criteria in UC and confirms that the prevalence of FGIDs is high. Patients with active disease and overlapping functional symptoms appear to have worse QoL and more psychological distress compared to those with quiescent disease. Clinicians should therefore be vigilant to this functional overlap and treat both functional and inflammatory driven symptoms.